(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
Artisanal gold mining is one of the anthropogenic activities identified by the United Nations Scientific Committee on the Effects of Atomic Radiation as potential source of exposure to naturally occurring radionuclides. 40 surface soil samples collected at random from Gababiyu artisanal gold mining site in Minna Metropolis were assessed for their natural radioactivity using gamma spectrometric technique which employs NaI (Tl) gamma-ray detector. Specific activities of 226Ra, 232Th and 40K in the soil varied from 10.27±2.88 to 152.60±3.80, 32.67±1.93 to 185.90±6.06 and 35.18±1.45 to 947.50±7.51 Bq kg-1 respectively, with mean values of 65.06±4.20, 87.63±2.89 and 267.94±4.29 Bq kg-1 in sequence. Although 226Ra and 232Th recorded activity values slightly above world average, they are still within safety range prescribed by UNSCEAR. Computed average absorbed dose rate at 1 m above ground was 94.16 nGy h-1 with corresponding mean annual dose equivalent of 0.12 mSv.y-1. Furthermore, calculated average excess lifetime cancer risk was found to be 0.40×10-3, which is slightly above the UNSCEAR safety limit. Pearson correlation statistics identified 226Ra and 232Th as principal radionuclides responsible for the computed radiation risk variables. Although the results of this investigation does not show any immediate radiological risk, continuous monitoring of the gold mining site is encouraged in order to keep the radiation effects as low as reasonably achievable.